Sexualities, gender and violence: a view from the Iberian Peninsula - Enguix Grau, Begoña (Human rights: contemporary issues and perspectives, 2020)
"The eleven essays and the introduction included in this collection offer an interdisciplinary reflection on the multifarious intersections of sexuality and gender-based norms in Southern Europe. They offer varied insights on the different negotiations of gender and sexuality and their connections to different forms of violence in the Iberian Peninsula. Empirically rich and theoretically challenging, the different chapters tackle topics such as the configuration of relationships, digital intimacies, sexual violence and harassment and sex education. The first part explores the current configurations of sexuality, gender and violence attending to traditional meanings and also to new debates on these issues. The second part explores current masculinities in relation to different forms of violence. This collection is essential reading for anyone who is interested in the relations between sex, gender and violence in the contemporary moment"--